Phase II trial of preoperative pemetrexed plus carboplatin in patients with stage IB-III nonsquamous non-small cell lung cancer (NSCLC). (April 2018) - Hainsworth, John D.; Waterhouse, David M.; Shih, Kent C.; Boccia, Ralph V.; Priego, Victor M.; McCleod, Michael J.; Kudrik, Fred J.; Mitchell, Reed Brian; Burris, Howard A.; Greco, F. Anthony; Spigel, David R.
Highlights: We evaluated neoadjuvant pemetrexed/carboplatin for patients with localized NSCLC. The drug combination was safe and feasible. The efficacy was similar to neoadjuvant regimens previously investigated. Further investigation requires a larger, randomized clinical trial. Abstract: Objectives: The combination of pemetrexed and carboplatin is a standard first-line treatment for patients with advanced NSCLC. In this pilot phase II trial, we evaluated the feasibility of using pemetrexed and carboplatin as neoadjuvant therapy, prior to definitive surgical resection, for patients with localized NSCLC. Patients and methods: Patients with potentially resectable, previously untreated, clinical stage IB-III, nonsquamous NSCLC were eligible for this trial. All patients received 4 cycles of pemetrexed (500 mg/m 2 ) and carboplatin (AUC 6.0) administered at 21 day intervals. Three to 6 weeks after completion of chemotherapy, definitive surgical resection was attempted. The primary endpoint of this trial was the 3-year survival rate. Results: Forty-six patients began protocol treatment, and 40 completed 4 courses of pemetrexed/carboplatin. Surgical resection was performed in 27 patients (59%); all had pathologic partial responses. The estimated 3-year survival rate for the entire group was 46%. Toxicity of neoadjuvant therapy was consistent with toxicity previously reported with pemetrexed/carboplatin. Conclusions: Administration of 4 courses of pemetrexed/carboplatin was feasible. The efficacy was similar to neoadjuvant regimens previously investigated. A significant number of patients 19 of 46 (41%) in this trial did not have surgical resection after neoadjuvant therapy. Further investigation of the role of neoadjuvant pemetrexed/carboplatin requires a larger, randomized clinical trial.